Anti-anxiety and hypnotic effects of ethanolic and aqueous extracts of Lippia citriodora leaves and verbascoside in mice - Marjan Razavi; Naser Zargarani; Hossein Hosseinzadeh (Mashhad University of Medical Sciences, 2017)
Objectives: The extract of Lippia citriodora and its main component, verbascoside, are known for their hypnotic effects in traditional medicine. In this study, the anxiolytic and hypnotic effects of L. citriodora leave extracts and verbascoside were evaluated in mice. Materials and Methods: Animals were divided into 11 groups of six mice each. Group I received normal saline, Group II received Diazepam (2 mg/kg) as positive control, Groups III, IV and V received L. citriodora ethanolic extracts (50, 100 and 200 mg/kg, respectively), Groups VI, VII and VIII received L. citriodora aqueous extracts (50, 100 and 200 mg/kg, respectively) and Groups IX, X and XI received Verbascoside (25, 50 and 100 mg/kg, respectively). All agents were administrated intraperitoneally. To evaluate hypnotic activity, pentobarbital sleeping test, and for anxiolytic activity, elevated plus-maze (EPM), locomotor activity, open field and motor coordination (rotarod test) tests were used. To understand the role of GABAA receptor, flumazenil was also administered. Results: The extracts and verbascoside increased the time spent and number of entries in the open arms of EPM. Moreover, these agents significantly increased the sleeping time induced by pentobarbital. In addition, the highest dose of extracts and verbascoside reduced time spent on the rod and total locomotion in the open field tests, respectively. Flumazenil inhibited the effects of extracts and verbascoside in EPM and hypnotic tests. Conclusion: These results suggested that ethanolic and aqueous extracts of L. citriodora and verbascoside exhibit anxiolytic, hypnotic and muscle relaxant effects especially at the highest doses and these effects are partially due to the interaction with GABAA receptor.